2005
DOI: 10.1111/j.1423-0410.2005.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of a World Health Organization Transfusion Basic Information Sheet to evaluate transfusion practice in Croatia

Abstract: The Basic Information Sheet can be incorporated into bedside clinical practice. We have identified the need to encourage clinicians to determine and document their transfusion targets before prescribing blood components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…Because of the limitations of our system in the informed consent of transfusion and examination of pre‐transfusion infectious diseases, after implementing BTMIS, the adequacy rate of transfusion medical records had increased from 74.8% to 90.4%. Although our adequacy rate of transfusion medical records was higher than the rates of 10.6% reported in a study from Germany and 80% reported by Skodlar et al [23, 24], other measures should be taken to further improve the adequacy.…”
Section: Discussioncontrasting
confidence: 79%
“…Because of the limitations of our system in the informed consent of transfusion and examination of pre‐transfusion infectious diseases, after implementing BTMIS, the adequacy rate of transfusion medical records had increased from 74.8% to 90.4%. Although our adequacy rate of transfusion medical records was higher than the rates of 10.6% reported in a study from Germany and 80% reported by Skodlar et al [23, 24], other measures should be taken to further improve the adequacy.…”
Section: Discussioncontrasting
confidence: 79%